2016
DOI: 10.1021/acs.macromol.6b01001
|View full text |Cite
|
Sign up to set email alerts
|

Specific Anion Effects on the Internal Structure of a Poly(N-isopropylacrylamide) Brush

Abstract: The effect of anion identity and temperature on the internal nanostructure of poly(N-isopropylacrylamide) brushes were investigated using neutron reflectometry (NR), atomic force microscopy (AFM) and quartz crystal microbalance with dissipation monitoring (QCM-D). NR and QCM-D measurements showed that addition of strongly kosmotropic acetate anions shifted the lower critical solution temperature (LCST) to lower temperatures relative to pure D2O/H2O, while strongly chaotropic thiocyanate anions shifted the LCST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
125
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(136 citation statements)
references
References 69 publications
11
125
0
Order By: Relevance
“…2 ) on the equilibrium thermoresponse of PNIPAAm brushes was studied using in situ ellipsometry, quartz crystal QCM-D, static contact angle measurements, neutron reflectometry (NR), and AFM [31,32]. It was found that the shift in transition temperature was in line with the Hofmeister series where transition temperature was shifted to lower temperature by kosmotropic acetate ions and higher temperature by chaotropic thiocyanate ions [31,32].…”
Section: The Effect Of Specific Anions (Scn − and Ch 3 Co −mentioning
confidence: 99%
See 2 more Smart Citations
“…2 ) on the equilibrium thermoresponse of PNIPAAm brushes was studied using in situ ellipsometry, quartz crystal QCM-D, static contact angle measurements, neutron reflectometry (NR), and AFM [31,32]. It was found that the shift in transition temperature was in line with the Hofmeister series where transition temperature was shifted to lower temperature by kosmotropic acetate ions and higher temperature by chaotropic thiocyanate ions [31,32].…”
Section: The Effect Of Specific Anions (Scn − and Ch 3 Co −mentioning
confidence: 99%
“…2 ) on the equilibrium thermoresponse of PNIPAAm brushes was studied using in situ ellipsometry, quartz crystal QCM-D, static contact angle measurements, neutron reflectometry (NR), and AFM [31,32]. It was found that the shift in transition temperature was in line with the Hofmeister series where transition temperature was shifted to lower temperature by kosmotropic acetate ions and higher temperature by chaotropic thiocyanate ions [31,32]. Koenig et al studied the effect of NaCl salt on the thermoresponsive behavior of PNIPAAm brushes using QCM and ellipsometry and found that transition temperature was shifted to lower temperatures by the addition of NaCl salt due to the interaction of the ions with the amide groups and the hindrance of hydrogen-bonding formation [33].…”
Section: The Effect Of Specific Anions (Scn − and Ch 3 Co −mentioning
confidence: 99%
See 1 more Smart Citation
“…PNIPAM brushes exhibit lower critical solution temperature (LCST) type behavior, undergoing a swollen to collapsed transition as the temperature increases above 32 C. Previous studies of PNIPAM brushes have observed a diffuse layer at low temperatures, which transitions through a two-phase swollen-collapsed state as the system temperature passes through its LCST at 32 C, before collapsing entirely above 32 C (Murdoch et al, 2016;Yim et al, 2004;. The PNIPAM system was chosen as it is well characterized and allows for a range of system conformations to be investigated for a single substrate and solvent combination.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of brushes are substantially determined by the polymer type, the length of the polymer chains, their grafting density, and the interactions between polymer chains and environment. Therefore, polymer brushes are widely used to tune the surface properties of materials and to render them, for example, superhydrophobic, highly hydrophilic, cell‐adhesive, antifouling, and other properties . They are also able to demonstrate switchable properties due to the stimuli‐responsive behavior of the polymer chains that were grafted onto the surface .…”
Section: Introductionmentioning
confidence: 99%